2018
DOI: 10.1155/2018/3041426
|View full text |Cite
|
Sign up to set email alerts
|

The Domination Complexity and Related Extremal Values of Large 3D Torus

Abstract: Domination is a structural complexity of chemical molecular graphs. A dominating set in a (molecular) graph G=V,E is a subset S⊆V such that each vertex in V\S is adjacent to at least one vertex in S. The domination number γG of a graph G is the minimum size of a dominating set in G. In this paper, computer-aided approaches for obtaining bounds for domination number on torus graphs are here considered, and many new exact values and bounds are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A perfect matching between two disjoint graphs G 1 , G 2 with the same order n is a matching consisting of n edges such that each of them has one end vertex in G 1 and the other one in G 2 . See [7][8][9][10][11][12][13][14].…”
Section: Definitions and Notationmentioning
confidence: 99%
“…A perfect matching between two disjoint graphs G 1 , G 2 with the same order n is a matching consisting of n edges such that each of them has one end vertex in G 1 and the other one in G 2 . See [7][8][9][10][11][12][13][14].…”
Section: Definitions and Notationmentioning
confidence: 99%
“…Graph domination and associated concepts have been studied for many years and there are more than 200 papers to study on the subject [2][3][4]. Among them, many authors study the domination number of products of graphs [5,6], especially for cylinders [7], torus [8,9] and grids [10]. Liu et al initiated the study of the domination number of two directed cycles, and they [11,12] determined the exact values of γ(C m C n ) for m up to 6 and showed that Theorem 1. γ(C m C n ) = mn 3 if m ≡ 0 (mod 3) and n ≡ 0 (mod 3).…”
Section: Introductionmentioning
confidence: 99%
“…There have been more than 200 papers studying various domination on graphs in the literature [2][3][4][5][6]. Among them, Roman domination and double Roman domination appear to be a new variety of interest [3,[7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%